Molecular detection and whole genome characterization of Canine Parainfluenza type 5 in Thailand - Kamonpan Charoenkul (Nature Portfolio, 2021)
Abstract Parainfluenza virus type 5 (PIV-5) causes respiratory infection in several animal species and humans. Canine parainfluenza virus type 5 (CPIV-5) causes respiratory disease in domestic dogs worldwide. In this study, we conducted a cross-sectional survey of CPIV-5 in dogs with respiratory symptoms from small animal hospitals in Thailand from November 2015 to December 2018. Our results showed that 32 out of 571 nasal swab samples (5.6%) were positive for CPIV-5 by RT-PCR specific to the NP gene. To characterize the viruses, three representative CPIV-5 were subjected to whole genome sequencing, and an additional ten CPIV-5 were subjected to HN, F, SH and V/P gene sequencing. Pairwise sequence comparison and phylogenetic analysis showed that Thai CPIV-5 was closely related to the CPIV-5 isolated from China and Korea. In conclusion, this study constitutes a whole genome characterization of CPIV-5 from dogs in Thailand. The surveillance of CPIV-5 should be further investigated at a larger scale to determine the dynamics, distribution and potential zoonotic transmission of CPIV-5.